Carbon Emissions Disclosure are Reviewed of Firm Characteristics, Environmental Performance and Women on the Board of Directors - Iislamiyah Iislamiyah; Novita Indrawati; Al Azhar L (Jurnal Akuntansi Aktual, 2024)
Purpose: This study aims to test and analyze the effect of company size, company age, environmental performance and women on the board of directors on the disclosure of carbon emissions in energy sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period.Method: The data analysis method used, namely multiple linear regression analysis. The sampling technique in this study used purposive sampling technique and obtained a sample of 60 companies, so that the number of observations was 180 observations.Findings: The results of this study indicate that company size and environmental performance affect the disclosure of carbon emissions. While the age of the company and women in the board of directors have no effect on the disclosure of carbon emissions.Originality/Value: The results of this research will most likely help companies develop their understanding of environmental issues, especially in disclosing carbon emissions These findings can assist companies in developing carbon emission management strategies by considering factors such as company size and environmental performance. In addition, the results of this study may increase corporate awareness of the importance of corporate sustainability in business practices.